Influence of different phosphorus sources and zinc spray on yield and quality of black pepper (Piper nigrum L.) under acid soils - Muthumanickam, D (Journal of Spices and Aromatic Crops, 2003)
Trials were conducted to identify the suitable form of phosphorus and optimum spray concentration of zinc for increasing yield of black pepper under acid soil conditions of Yercaud (Tamil Nadu, India). The results indicated that soil application of 40 g P2O5 vine-1 as rock phosphate along with spraying of ZnSO4 (0.5%) increased dry pepper yield (9.21 kg vine-1) and oleoresin content (12.34%).